A painful hip as a presentation of Guillain-Barré syndrome in children. Issue 7279 (20th January 2001) - Tang, Tjun; Noble-Jamieson, Charles
Abstract : Guillain-Barré syndrome should be part of the differential diagnosis of children with painful lower limbs